Transarterial chemoembolization (TACE) combined with donafenib as first-line therapy for unresectable hepatocellular carcinoma (uHCC): A real-world clinical study - Zhu, Bowen; Tang, Yiyang; Xue, Miao; Wu, Yanqin; Zhao, Yue; Fan, Wenzhe (Journal of clinical oncology, 2024)
e16145Background: To evaluate the efficacy and safety of TACE combined with Donafenib, which is as a new tyrosine kinase inhibitors therapy recommended by the China liver cancer staging (CNLC) system for the treatment of unresectable hepatocellular carcinoma (uHCC). Methods: We conducted a single-center, retrospective study on patients diagnosed with uHCC treated by TACE plus Donafenib as the first-line therapy between May 2021 and September 2023 at The First Affiliated Hospital of Sun Yat-sen University. The primary outcomes evaluated in this study were progression-free survival (PFS) and overall survival (OS). Local response, one-year survival rate, safety and tolerability were the secondary outcomes. Results: All of 48 eligible patients by August, 2023, with the median age of 59 years. The clinical characteristics were as follows: BCLC stage A:2 (4.2%), B:16 (33.3%), and C:30 (62.5%); Child-Pugh class A:33 (68.8%) and B:15 (31.2%); ECOG PS 0: 27 (56.2%) and 1: 21 (43.7%). In this study, 10 (20.8%) patients had huge intrahepatic lesions, 15 (31.2%) subjects exhibited extrahepatic metastases at multiple sites, 19 (42.2%) patients presented with portal vein tumor thrombus, and 4 patients were diffuse-type HCC.107 TACE sessions were performed. Three patients had liver transplantation as frequent therapy, and histopathological examination of tissue from these subjects revealed complete necrotic foci. The median PFS was 12.8 months (95% CI: 8.66-NA) , mOS was not reached and the one-year OS rate was 87.5% (95% CI: 77%-97%) in the survival results. The tumor objective response rate was 58.3% with 14.5% complete response and 43.7% partial response based on mRECIST assessment. The disease control rate of the study group was 81.3%. The most common treatment-related adverse events (TRAEs) observed were elevated aspartate aminotransferase (AST) levels (75.0%), increase in bilirubin level (72.9%), elevated alanine aminotransferase (ALT) levels (54.2%), hand-foot syndrome (53.1%), diarrhea (29.1%), rashes (22.9%), hair loss (18.4%) and hypertension (12.5%). Twenty-three (46.9%) patients presented with grade 3 or 4 TRAEs including elevated AST levels (22.4%), elevated ALT levels (16.3%), increase in bilirubin level (4%), diarrhea (4%) and hypertension (2%). No Grade 5 TRAEs were observed. Conclusions: The combination of TACE and Donafenib presented good efficacy and tolerability, which could be potentially used as the first-line treatment of Chinese uHCC patients.